Electro-Enhanced Gas Fermentation for Bioproduction of Volatile Fatty Acids and Alcohols - Clemens Hiebl; Werner Fuchs (Microorganisms)
This study investigates sub-stoichiometric electron supply, also termed electro-fermentation, to influence product formation in gas fermentation. Two species, Clostridium carboxidivorans and Alkalibaculum bacchi, as well as a co-culture of A. bacchi and Clostridium kluyveri, were tested in batch cultures with and without an external cell potential of 800 mV. The supplied gas mixture was 50:40:10 N2:H2:CO2. The test unit was a single-chamber reactor with a cathode made from an electrically conducting composite of PP and black carbon. The observed current densities were generally very low, around 0.22 mA/m2. Despite that, a significant and reproducible change in product patterns and formation rates occurred. C. carboxidivorans increased the formation of acetate (+32%), butyrate (+300% relative to the control), and caproate (+600% relative to the control). In a similar manner, A. bacchi produced more acetate (+38%), butyrate (13 times more than the control), and caproate (only observed in the electrified setup). Additional trials using a modified gas phase composition, 80:20 H2:CO2, confirmed the finding that the application of an electric potential enhances chain elongation as well as alcohol formation. Moreover, an experiment with reversed electric polarity showed that a high cathode surface area is essential for inducing metabolic modifications. The results demonstrate that electro-fermentation holds significant potential for improving bioconversion processes aimed at producing green chemicals.